2007
DOI: 10.4049/jimmunol.178.9.5820
|View full text |Cite
|
Sign up to set email alerts
|

MyD88-Mediated Instructive Signals in Dendritic Cells Regulate Pulmonary Immune Responses during Respiratory Virus Infection

Abstract: Respiratory syncytial virus (RSV) is the leading cause of respiratory disease in infants worldwide. The induction of innate immunity and the establishment of adaptive immune responses are influenced by the recognition of pathogen-associated molecular patterns by TLRs. One of the primary pathways for TLR activation is by MyD88 adapter protein signaling. The present studies indicate that MyD88 deficiency profoundly impacts the pulmonary environment in RSV-infected mice characterized by the accumulation of eosino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
56
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 52 publications
5
56
2
Order By: Relevance
“…Production of IL-12 is thought to favor differentiation and function of (Th1) T cells while inhibiting the differentiation of Th2 cells. In many viral infections, IL-12 promotes viral clearance and host recovery from infection (71)(72)(73)(74).…”
Section: Discussionmentioning
confidence: 99%
“…Production of IL-12 is thought to favor differentiation and function of (Th1) T cells while inhibiting the differentiation of Th2 cells. In many viral infections, IL-12 promotes viral clearance and host recovery from infection (71)(72)(73)(74).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the type of inflammatory environment generated during these early signaling events likely alters subsequent T-cell responses, because susceptible infants exhibit characteristics of Th2 responses (6). Since recent findings have implicated TLR-mediated inflammation in the immunopathogenesis of RSV disease, emphasis has been placed on understanding how TLRs can influence immune responses against RSV (3,7,28,36,39,50).…”
Section: Discussionmentioning
confidence: 99%
“…We observed a decrease in activated lung DCs (CD11b hi CD11c hi CD86 ϩ ) in TLR2 KO mice at 24 and 48 h postinfection, suggesting that TLR2-mediated signals generated during RSV infection could influence DC activation. Interestingly, Rudd et al showed that a lack of MyD88-dependent signaling in DCs can promote Th2 responses after RSV infection (39). Additionally, TLR2 signaling may further contribute to RSV responses by facilitating interactions between DCs and neutrophils that can further shape T-and B-cell polarization (34).…”
Section: Discussionmentioning
confidence: 99%
“…2) [18][19][20][21][22][23]. Furthermore, when overexpressed on APC or when crosslinked as fusion proteins, DLL ligands promote T H 1 cell differentiation [18,20,22,[24][25][26].…”
Section: Induction Of T H 1-cell Differentiation By Notchmentioning
confidence: 99%